ANALISIS PENANGANAN KREDIT MACET - Luluk Ambarsita (Manajemen Bisnis, 2013)
Luluk AmbarsitaProgram Studi Manajemen FEB UMME-mail: lu2k_412sita@yahoo.comABSTRACTNon-performing loans are loans with certain risks caused by debtor’s failure to perform his/herobligations. In banking activities, non-performing loan could be affected by internal as well asexternal factor. The risk of non-performing loan will be reduced considerably by the prudentialprinciple and other credit analysis principles are fully followed by bank as the creditor. This describeshow the bank especially PT BRI (Persero) Tbk. Branch at Lamongan, managed and approvedthe applications of loan submitted by its prospective debtors. The models and methods used by thebank to handle credit default were also explored in this study. To deal with non-performing loan, PTBRI (Persero) Tbk. Lamongan Branch used several methods, namely Credit restructuration, amicablesettlement involving the direct selling of collateral as well as legal settlement involving KPKNL (TheOffice for State Assets and Auction Service) were utilized to handle credit default.Keywords: Non-performing loan, credit default, credit settlement